Cardiovascular Outcome in Patients Treated With SGLT2 Inhibitors for Heart Failure: A Meta-Analysis - Gager, Gloria M.; Gelbenegger, Georg; Jilma, Bernd; von Lewinski, Dirk; Sourij, Harald; Eyileten, Ceren; Filipiak, Krzysztof; Postula, Marek; Siller-Matula, Jolanta M. (Frontiers in Cardiovascular Medicine, 2021)
Background; Sodium-glucose cotransporter 2 (SGLT2) inhibitors are an emerging class of glucose lowering drugs, which become increasingly relevant for treatment and prevention of heart failure (HF). Therefore we aimed to investigate various SGLT2 inhibitors in patients with established HF at baseline. Methods: Extensive search of PubMed and Web of Science until January 2021. Two reviewers independently and in duplicate applied the selection criteria. This meta-analysis was conducted according to the PRISMA guidelines. Data was pooled using a random-effects model. Randomized controlled trials (RCT) of SGLT2 inhibitors vs comparator in patients with HF reporting clinical outcomes. The primary efficacy outcome was the composite of hospitalization for HF (HHF) or cardiovascular (CV) mortality. All-cause mortality, CV mortality and HHF were considered as secondary endpoints. Subgroup analyses involving status of diabetes, type of HF, administered type of SGLT2 inhibitor, sex, age, BMI, eGFR, cause of HF and concomitant medication were performed. Results: Seventeen RCTs, comprising a total of 20749 participants, were included (n=10848 treated with SGLT2 inhibitors and n=9901 treated with a comparator). Treatment with SGLT2 inhibitors in a HF population was associated with a 27% relative risk reduction (RRR) of HHF or CV-mortality (RR=0.73, 95%CI: 0.68-0.78); 32% RRR of HHF (RR=0.68, 95%CI: 0.62-074); 18% RRR of CV mortality (RR=0.82, 95%CI: 0.73-0.91) and 17% RRR of all-cause mortality (RR=0.83, 95%CI: 0.75-0.91). The effect of SGLT2 inhibitors on the primary endpoint was consistent among the SGLT2 types. The effect of SGLT2 inhibitors on the primary endpoint was independent from underlying diabetes mellitus, age, sex, BMI, renal function and HF type. Conclusions: SGLT2 inhibitors are associated with improved CV outcome in patients with HF.